2015
DOI: 10.3390/ijms161024032
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a Inhibits the Epithelial—Mesenchymal Transition of Podocytes through Downregulation of NFATc3

Abstract: MicroRNAs (miRNAs) possess an important regulating effect among numerous renal diseases, while their functions in the process of epithelial-to-mesenchymal transition (EMT) after podocyte injury remain unclear. The purpose of our study is to identify the potential functions of miR-30a in EMT of podocytes and explore the underlying mechanisms of miR-30a in the impaired podocytes. The results revealed that downregulation of miR-30a in podocyte injury animal models and patients, highly induced the mesenchymal mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…HG addition is able to induce the increase of micro-RNA-346 which is a concentration-dependent effect, and miR-346 mimic significantly inhibits EMT of podocytes by indirectly decreasing the expression of GSK-3β [38]. In podocytes, miR-30a significantly enhanced the expression of E-cadherin, an EMT marker, blocking the podocyte EMT by targeting NFATc3 [39]. These studies indicate that miRNAs play a pivotal role in regulating podocyte EMT.…”
Section: Discussionmentioning
confidence: 75%
“…HG addition is able to induce the increase of micro-RNA-346 which is a concentration-dependent effect, and miR-346 mimic significantly inhibits EMT of podocytes by indirectly decreasing the expression of GSK-3β [38]. In podocytes, miR-30a significantly enhanced the expression of E-cadherin, an EMT marker, blocking the podocyte EMT by targeting NFATc3 [39]. These studies indicate that miRNAs play a pivotal role in regulating podocyte EMT.…”
Section: Discussionmentioning
confidence: 75%
“…Angiotensin II has been shown to induce calcineurin signaling and podocyte injury by reducing miR-30, indicating that miR-30 expression might be protective for podocyte [51]. miR-30e has been shown to target Bnip3L and protect against aldosterone-induced podocyte apoptosis and mitochondrial dysfunction [52]. miR-30a has also been shown to inhibit EMT of podocyte through downregulation of NFATc3 [53].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
“…Peng et al . 16 reported that miR‐30a can inhibit the epithelial–mesenchymal transition. Zhu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Du et al [13] identified 18 downregulated and 19 up-regulated miRNAs in fibrotic livers, of which miR-30a was down-regulated in a NASH model in C57BL/6 mice, and studies have reported that miR-30a is a key regulator of myocardial fibrosis [14] and peritoneal fibrosis [15]. Peng et al [16] reported that miR-30a can inhibit the epithelial-mesenchymal transition. Zhu et al [17] reported that Beclin1, a key autophagy-related gene, was a possible target for miR-30a, which negatively regulated Beclin1 to inhibit autophagic activity.…”
Section: Introductionmentioning
confidence: 99%